Development and Evaluation of a DNA Vaccine Encoding 31-KDA Outer Membrane Protein of Brucella Melitensis - Ashrafzadeh, Seyed Parham (2009)

(untitled)
Brucellosis is a widespread disease affecting livestock and humans caused by Brucella spp., which are facultative, Gram negative intracellular pathogens. In Malaysia brucellosis is prevalent especially in animals, which can cause abortion and consequent economic losses. The live attenuated strains like Brucella melitensis Rev1 and B. abortus S19 and RB51 are being used to control brucellosis in domesticated animals however they have some disadvantages, such as these strains provoke antibodies to their lipopolysaccharide (LPS), making it difficult to distinguish vaccinated animals from those naturally infected. The DNA vaccines offer a new approach because they can stimulate both cellular and humoral immunities. On the other hand, DNA vaccines have many advantages over traditional protein-based vaccines, such as ease of development, inducing a long lived immunity, and minimal preparation costs. On account of the fact that, vaccination is the only way to control and eradicate the disease, the vaccine which can induce antibody in animals and protect them from infection and can overcome the drawbacks of current live attenuated vaccines, is essential. In this study, the outer membrane proteins (Omps) of Brucella melitensis 152, 183 and 293 of local isolates were extracted and characterized using Sodium Dodecyl Sulfate-polyacrylamide Gel Electrophoresis (SDS-PAGE). Accordingly, all the strains showed major bands were approximately 22, 23, 31, 43 and 94 kDa and minor bands were approximately 10, 16, 19, 73 kDa. Immunoblotting was conducted using antisera against the whole cells of B. melitensis 183 revealed the antigenicity of Omps of the three isolates. Omp31 was one of the antigenic proteins, chosen as a candidate for this research. Omp31 gene from all isolates was amplified, cloned in pcDNA3.1 (+) and sequenced. All isolates produced a single DNA fragment approximately at 723 bp. The sequence of all isolates was compared with the published sequences to show the percentage of the similarity to them which displayed 100% similarity of strain 183, 99.8% of strain 152, and 99.8% of strain 293 to strain 16M as the reference strain. To study the immunization of Omp31, DNA vaccination method applied as a novel approach for vaccination in BALB/c mice. The mice were divided into four groups: vector with insert (pcDNA3.1-Omp31), vector alone (pcDNA3.1), PBS and unvaccinated group. In conclusion, Immunization with pcDNA3.1-Omp31 elicited antibody response which was detectable 30 days after the first immunization. However, No antibody response was detected against other control groups.